The iPeer2Peer Program: a pilot randomized controlled trial in adolescents with Juvenile Idiopathic Arthritis. Issue 1 (December 2016) - Stinson, Jennifer; Ahola Kohut, Sara; Forgeron, Paula; Amaria, Khush; Bell, Mary; Kaufman, Miriam; Luca, Nadia; Luca, Stephanie; Harris, Lauren; Victor, Charles; Spiegel, Lynn
Abstract Background Adolescents with Juvenile Idiopathic Arthritis (JIA) are at risk for physical, emotional, social and role challenges that negatively impact quality of life. Peer mentoring has been shown to improve positive health behaviours in adolescents with chronic disease while simultaneously providing social support. The objectives of this paper are to examine the feasibility and acceptability of an online peer mentoring program (iPeer2Peer Program) for adolescents with JIA. Methods The iPeer2Peer program was examined using a waitlist pilot randomized control trial (RCT). Participants were randomly allocated to the intervention or wait-list control group via a secure, web-based randomization service. Health care providers and investigators were blinded to participant group allocation. Trained peer mentors (16–25 years; successfully managing their JIA) were matched to participants (12–18 years; diagnosed with JIA) randomized to the intervention group to provide peer support and education for effective self-management of JIA. Participant-mentor pairings connected ten times over 8 weeks using Skype video calls. Primary outcomes focused on implementation (i.e. measures of feasibility and acceptability). Secondary outcomes focused on effectiveness (i.e. measures of self-management, self-efficacy, pain, social support and quality of life). Results Thirty adolescents (mean age 14.3 ± 1.7 years, 97 % female) completed the RCT (interventionn  = 16, controln  = 14).Primary outcomes: One third (32 %) of adolescents approached agreed to participate, completed baseline measures and were randomized. Half of pairings completed ten calls within 8 weeks. Average call length was twice the required amount with call lengths of 44.72 ± 15.76 min. Participants reported satisfaction with the program and all reported that they would recommend it to their peers. Participants' mean engagement level with the program was 8.53/10 (range = 7–10).Secondary outcomes: Participants who completed the iPeer2Peer Program demonstrated improvements in their perceived ability to manage JIA (p  < 0.04), compared to controls. No adverse events were reported. Conclusion The iPeer2Peer Program is a promising intervention that improves acceptability of self-management and peer support treatments for adolescents with JIA. By using the Internet to connect mentors to adolescents with JIA it may also improve accessibility to these resources. Findings will be used to adapt the program and refine the methodology for a full-scale RCT. Trial registration ClinicalTrials.gov Identifier:NCT01986400 . Registered November 11, 2013.